2015
DOI: 10.1038/ncomms8815
|View full text |Cite
|
Sign up to set email alerts
|

Condensin targets and reduces unwound DNA structures associated with transcription in mitotic chromosome condensation

Abstract: Chromosome condensation is a hallmark of mitosis in eukaryotes and is a prerequisite for faithful segregation of genetic material to daughter cells. Here we show that condensin, which is essential for assembling condensed chromosomes, helps to preclude the detrimental effects of gene transcription on mitotic condensation. ChIP-seq profiling reveals that the fission yeast condensin preferentially binds to active protein-coding genes in a transcription-dependent manner during mitosis. Pharmacological and genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(160 citation statements)
references
References 70 publications
7
152
1
Order By: Relevance
“…Although we have been unable to obtain any crystals with a longer stretch hCAP‐H, our DNA binding assay clearly showed that hCAP‐H is indeed required to make DNA‐binding surface together with hCAP‐G. It remains unknown whether the ability of the hCAP‐G‐H subcomplex to interact with ssDNA, which was not observed for its yeast counterpart, may be related to the previously proposed function of condensin I in transcribing regions to regenerate dsDNA . In the future, it will be important to further clarify the similarities and detailed differences in the structure and function of this fundamental chromosome organizing machinery among different eukaryotic species.…”
Section: Resultsmentioning
confidence: 75%
“…Although we have been unable to obtain any crystals with a longer stretch hCAP‐H, our DNA binding assay clearly showed that hCAP‐H is indeed required to make DNA‐binding surface together with hCAP‐G. It remains unknown whether the ability of the hCAP‐G‐H subcomplex to interact with ssDNA, which was not observed for its yeast counterpart, may be related to the previously proposed function of condensin I in transcribing regions to regenerate dsDNA . In the future, it will be important to further clarify the similarities and detailed differences in the structure and function of this fundamental chromosome organizing machinery among different eukaryotic species.…”
Section: Resultsmentioning
confidence: 75%
“…Mitotic defects caused by the condensin mutation are suppressed by inhibiting Pol III and Pol II transcription (Iwasaki et al 2010; Sutani et al 2015). Note that this condensin mutation is temperature-sensitive and partially impairs condensin activity.…”
Section: Condensin-tbp Mechanism Links Transcription and Chromosome Omentioning
confidence: 99%
“…Our study suggests that the kleisin subunit of the human condensin I complex, hCAP-H (Cnd2 cognate), interacts with human TBP (Iwasaki et al 2015a). As in fission yeast cells, condensin is enriched at highly transcribed genes in higher eukaryotes (Kim et al 2013; Sutani et al 2015). It has recently been shown that condensin mediates gene looping and activation in human cells, and that condensin mutations are significantly accumulated in various cancer types (Li et al 2015; Leiserson et al 2015).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Condensin is recruited to highly transcribed genes, probably by targeting unwound DNA segments [55]. The RPA mutation that suppresses the cohesion defect was originally identified as suppressor of a temperature-sensitive condensin mutant in fission yeast [56].…”
Section: Dna-dna Interactions: How To Tethermentioning
confidence: 99%